“Belanda Setan” Enters Hiang: The Dutch East Indies Government's Invasion of Kerinci in 1903 - Hudaya, Padhil (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
Kerinci was an area that was not touched by the Dutch East Indies Government. The Dutch East Indies government initially tried to "persuade" the top officials in Kerinci to agree to collaborate. This collaboration was highly hoped for by the Dutch East Indies Government, considering Kerinci's abundant natural resources. This research aims to see how the Dutch East Indies Government tried to incorporate Kerinci into the Dutch East Indies Government's administrative area through war, which focuses on how the people in Mendapo Hiang resisted the invasion. The method used in this paper is to apply the stages of the historical method, which include source collection, source criticism, interpretation and historiography. From this research it can be seen that efforts to establish cooperation by the Dutch East Indies were met with rejection after rejection by Kerinci officials, so that in the end the Dutch Indies Government sent a "military expedition" troop. One of the resistances that took place occurred in Mendapo Hiang, through a war that lasted for several days. Nevertheless, the people of Mendapo Hiang who resisted had to accept defeat in the war, and were forced to accept the existence of the Dutch East Indies in their territory.